2012
DOI: 10.1093/jxb/ers296
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-responsive transcription factors interact with promoters of ADH and PDC involved in persimmon (Diospyros kaki) fruit de-astringency

Abstract: The persimmon fruit is a particularly good model for studying fruit response to hypoxia, in particular, the hypoxia-response ERF (HRE) genes. An anaerobic environment reduces fruit astringency by converting soluble condensed tannins (SCTs) into an insoluble form. Although the physiology of de-astringency has been widely studied, its molecular control is poorly understood. Both CO2 and ethylene treatments efficiently removed the astringency from ‘Mopan’ persimmon fruit, as indicated by a decrease in SCTs. Aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
180
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(192 citation statements)
references
References 45 publications
5
180
3
1
Order By: Relevance
“…Transient overexpression of DkPDC2 in persimmon leaves resulted in lower SCTs content [12]. In addition, several hypoxia-responsive ERF transcriptional regulator genes were also isolated, including DkERF4 , DkERF5 , DkERF9 and DkERF10 [12], [13], but only DkERF9 and DkERF10 activated the promoters of DkPDC2 and DkADH1 , respectively [12]. These results suggested that ERF genes are involved in transcriptional regulation of persimmon fruit deastringency, and also expanded the functional changes involving ERF genes, which also include texture [14][16], carotenoids [17], ethylene [18], senescence [19] and stress response [20].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Transient overexpression of DkPDC2 in persimmon leaves resulted in lower SCTs content [12]. In addition, several hypoxia-responsive ERF transcriptional regulator genes were also isolated, including DkERF4 , DkERF5 , DkERF9 and DkERF10 [12], [13], but only DkERF9 and DkERF10 activated the promoters of DkPDC2 and DkADH1 , respectively [12]. These results suggested that ERF genes are involved in transcriptional regulation of persimmon fruit deastringency, and also expanded the functional changes involving ERF genes, which also include texture [14][16], carotenoids [17], ethylene [18], senescence [19] and stress response [20].…”
Section: Introductionmentioning
confidence: 98%
“…Transient overexpression of DkPDC2 in persimmon leaves resulted in lower SCTs content [12]. In addition, several hypoxia-responsive ERF transcriptional regulator genes were also isolated, including DkERF4 , DkERF5 , DkERF9 and DkERF10 [12], [13], but only DkERF9 and DkERF10 activated the promoters of DkPDC2 and DkADH1 , respectively [12].…”
Section: Introductionmentioning
confidence: 99%
“…Plant responses to anoxia involve a range of metabolic and morphological changes on different timescales, including rapid induction of anaerobic metabolism (Kennedy et al ., ; Voesenek and Bailey‐Serres, ). For persimmon ( Diospyros kaki ), the anaerobic metabolite acetaldehyde, which accumulates under high CO 2 treatment (95%), participates in fruit postharvest deastringency by converting the soluble tannins to insoluble products (Min et al ., ; Pesis and Ben‐Arie, ; Taira et al ., , ). However, deastringency is usually also accompanied by rapid fruit softening (Arnal and Del Río, ; Yin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, on account of some superior characteristics such as simplicity, easy performance and cost saving, the Agrobacterium-mediated transient gene expression system has been wildly used for characterization of genes function in herb and woody plants (Li et al, 2009;Wydro et al, 2006;Orzaez et al, 2006;Figueiredo et al, 2011). So far, only one study has reported that a transient expression system according to the protocols used for tobacco was applied in persimmon (Min et al, 2012). However, to our knowledge, no system of transient gene expression for persimmon has been specially established.…”
Section: Introductionmentioning
confidence: 99%